Meta-Analysis of NHT and STAD Learning Models on Elementary School Students' Mathematical Cognitive Learning Outcomes - Susi Lasmana Dewi; Tego Prasetyo (EduBasic Journal: Jurnal Pendidikan Dasar, 2021)
Many studies showed the influence of the NHT and STAD learning models on the elementary school students’ mathematics learning outcomes. It is necessary to conduct a thorough re-analysis in a study to see how much influence the NHT and STAD learning models have on students’ mathematics learning outcomes with meta-analysis techniques. This study aims to determine the effect of the two learning models from various published experimental studies on mathematics learning outcomes. This study employed a meta-analysis method. The first step was to determine the problem, then searched the research articles' data on the internet through Google Scholar. The search results found 20 matching articles. The NHT learning model showed a mean increase of 82.31%, greater than the STAD learning model with 78.59%. The prerequisite test using the normality, homogeneity, and linearity tests revealed that the two learning models were normally distributed, homogeneous, and linear. The normality test utilizing the Shapiro-Wilk technique obtained a significance value of 0.05. The pre-test data homogeneity test showed Sig. 0.081 0.05, while the post-test data revealed Sig. 0.444 0.05. The linearity test of the two learning models uncovered a significance value of 0.05. Besides, the ANCOVA test with univariate showed that the Partial Eta Squared value was 0.210, with Sig. 0.042 0.05, meaning that H0 was rejected, and Ha was accepted. The results showed that there were significant differences. Effect size calculation revealed that the NHT and STAD learning models had a relatively small effect on mathematics learning outcomes.